Intravenous immunoglobulin treatment in chronic inflammatory demyelinating polyradiculoneuropathy, a time to start and a time to stop. Issue 3 (September 2016) - Adrichem, Max E.; Eftimov, Filip; van Schaik, Ivo N.
Abstract: Intravenous immunoglobulin (IVIg) is often used as preferred treatment in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Several studies highlighted the short‐term efficacy of IVIg for CIDP yet many patients need maintenance therapy. Notwithstanding the fact IVIg has been used for over 30 years in CIDP, there is only limited evidence to guide dosage and interval during maintenance treatment. The variation in disease course, lack of biomarkers, and fear of deterioration after stopping IVIg makes long‐term treatment challenging. Recent studies suggest a proportion of patients receive unnecessary IVIg maintenance treatment. This review provides an overview of the use of IVIg for CIDP treatment, focusing on evidence for long‐term IVIg use.